Between Casuistry and Vagueness – A Comparative Legal Analysis of Employer Surveillance of Employee Tasks under Polish and Czech Legislation - Mirosławski, Tomasz (Central European Academy Law Review, 2025)
The new phase of economic development has brought many benefits to the countries of Central and Eastern Europe, yet rapid technological advancements also present inherent risks. While modern technologies have made it significantly easier for employers to fulfil their control entitlements and more efficiently protect their property, they concurrently pose threats towards employee privacy and dignity. The employee cannot be objectified and treated as a tool of the employer, and nor can his or her work be treated as a mere market commodity. The employer must respect the employee’s dignity and right to privacy, and should not infringe it by excessive surveillance. The relationship– which can also be classified as a conflict between the interests of the employer and the privacy of the employee – underscores the necessity of striking a certain balance between the two. Legal measures regulating workplace surveillance serve this purpose, albeit with variations across different countries. This article aims to analyse models of employee tasks surveillance in two countries in the Central and Eastern European region: the Czech Republic and Poland. Despite the similar paths followed by the labour law systems of both countries, the regulations concerning employee tasks surveillance exhibit significant divergence. The Polish model of workplace surveillance can be described as detailed yet narrow, while the Czech one can be referred to as open guidance, and sometimes even as a puzzle. Therefore, the focal point of the research is to compare the differences between these models. To achieve this, an exhaustive analysis was conducted of the doctrine, jurisprudence and provisions of legal acts regulating the issue of employee surveillance in both countries.